Service Innovation: Halal Logistics Intention Adoption Model - Zuhra Junaida Mohamad Husny Hamid; Muhammad Zaly Shah Muhammed Hussien; Mohd Iskandar Illyas Tan (International Journal of Supply Chain Management, 2017)
The concept of Halalan Toyyibban in halal product value chain has increasingly accepted among Muslim community. Halal logistics is the key factor for this concept to be materialized. Therefore, it is crucial for halal logistics to be adopted by halal product producer to uphold the integrity of their product throughout the whole supply chain process. Its vey alarming that still huge number of Malaysian Halal small medium enterprises (SMEs) still not adopting halal logistics. Therefore, this shows the important of this study to be conducted to identify factors that influence the intention of SMEs to adopt halal logistics services (HLS). Three objectives were established. Firstly, investigate the current state of halal logistics adoption among SMEs. Hypotheses derived were based on seven factors acquired: familiarity with innovation, status characteristics and position in social network, benefits, geographical setting, societal culture and political condition. The second objective is to determine the significant factors that influence SMEs intention to adopt HLS. Lastly, final objective is to proposal of an adoption intention model able to significantly predict the adoption intention of HLS among Malaysian SMEs. With extensive data collection, this study has succeeded in stipulating evidence to show: (1) being in the same social group HLS players and being familiar on HLS will significantly influence SMEs to adopt HLS, (2) being positioned in the same group of HLS actors will result in higher accessibility to information on HLS and (3) understanding of HLS benefits versus cost and with good support from the government are the necessary enablers of adoption of HLS among Malaysian SMEs. This research has also contributed to future service innovation adoption researches by providing an instrument to measure intention adoption service innovation model